PENGARUH BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA KARYAWAN PT. TIGA PUTRI JAYA PALEMBANG - Fane, Sugeng Mianto (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The purpose of this study was to determine the effect of organizational culture and commitment to the performance of employees of PT. Tiga Putri Jaya Palembang. Research samples of 43 employees were taken by the census method. Data collection using a questionnaire.The problem in this research is whether the organizational culture and commitment have a partial and simultaneous effect on the performance of the employees of PT. Tiga Putri Jaya Palembang? Hypothesis testing uses multiple linear regression analysis, through the T and F tests with a view to knowing the effect of the independent variable on the dependent variable at the 95% confidence level (a = 0.05).The test results on organizational culture variables have a positive effect on performance, it can be seen from the value of t arithmetic (3.055)> t table (2.021), on the commitment variable has a positive effect on performance, it is seen from the value of t arithmetic (2.734)> t table (2,021) , while the testers simultaneously obtained the value of t arithmetic (9,929)> t table (3,231), then the organizational culture and commitment variables affect the performance.